PENGARUH LATIHAN WALL PASS TERHADAP KEMAMPUAN SHORT PASS PERMAINAN SEPAK BOLA SISWA EKSTRAKURIKULER SEPAKBOLA SMP NEGERI 4 SIAK HULU KABUPATEN KAMPAR - Zulfi, Riski; Wijayanti, Niputu Nita; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was motivated by the perception of footballextracurricular activities SMP Negeri 4 Siak Hulu Kampar, the researchers found anumber of problems, among others, are: a) the basic techniques of football studentsenough, but still less than the maximum b) Passes to the fact that students are weakseveral times passing even less precise, c) The level of cooperation is still less than themaximum in fact only briefly ball in one hand easily caught, and vice versa. d) thefootball infrastructure is still insufficient in practice, the number of balls just a little,and others. The aim of this study was to determine the ability of the practice wall passshort pass game of football extracurricular student SMP Negeri 4 Siak Hulu. This studydirenacanakan place in SMP Negeri 4 Siak Hulu Kampar regency. This studydirenacanakan time for a month with 16 sessions in April and May 2015. The study is aresearch experiment. The population in this study are all members of the footballextracurricular SMP Negeri 4 Siak Hulu Kampar which amounted to 15 people. Thesample in this study took the entire population. Whereby the number of samples in thisstudy were 15 people.Based on the test results t-test calculation obtained t value at 3:23. The value isthen compared with the value table t. T table value at n = 15 or df = 14, at the level of5% error is 2.14. the results of the comparison value with the value t Atara table t asfollows: 3:23> 2.14. Based on the above equation in mind that the alternativehypothesis that reads There is the influence of exercise on the ability of the wall passshort pass game of football extracurricular student SMP Negeri 4 Siak Hulu acceptable.Keyword : Wall pass training, Short pass ability, foot ball2